Appraising Students’ Attitude towards Online Learning During Covid-19 Pandemic - SORAYA GRABIELLA DINAMIKA (Master Program in Linguistics, Diponegoro University, 2022)
This study aimed at evaluating the students’ attitude toward online learning during the Covid-19 pandemic within the written discourse by using the Appraisal Theory arranged by Martin & White, under the region of appreciation. Appreciation dealt with the evaluation of semiotic and natural phenomena. The realization of appraising item was adjectival that might have either positive or negative meaning. The data were obtained from the essays written by 25 students who joined the conversation subject through the online classroom. This study engaged with the qualitative descriptive method. The objectives of this study were three extents: (a) to find out the most predominant appreciation items the students tried to convey, (b) to find out the students’ value position, and (c) to give the pedagogical suggestion on the online learning. The result of the analysis showed that within 137 appraising items found, the positive appraising item exceeded the account of 52,5%. It reflected that the students had positive attitude toward online learning activities. Moreover, the students presented their value position as agreeing with the activity of online learning. Therefore, constructive pedagogical suggestions were given to the lecturers, the students, and the institution stakeholders.